FINANCIAL SECURITY OF SMALL BUSINESS ENTITIES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the peculiarities of functioning of modern small business in the field of small entrepreneurship under conditions of uncertainty, in particular, under martial law. It is substantiated that small business is a catalyst for investment activity in the country, a factor in the formation of a competitive economy, employment and income of the population, and thus - ensuring the financial security of the country as a whole. The authors identify the essence of small entrepreneurship and establish its typological characteristics, taking into account the peculiarities of financial activity. The authors conceptualize the theoretical basis for the financial security of business entities in the field of small business. The author's own approach to the definition of the concept of "financial security of small businesses" is proposed, which consists in the functioning of a system of the most efficient formation and use of financial resources of a small enterprise, which ensures the protection of the financial interests of its owners, timely identifies and neutralizes external and internal threats and risks of financial activity in order to achieve financial balance in the enterprise. The main components of the concept of "financial security of small business entities" are identified, which include: subjects, objects, threats and risks, typological features, principles and functions, and each of these elements is characterized. It is noted that the allocation of such basic components of financial security of small business entities allows for a deeper understanding of the mechanism of its provision, as well as identifying problems of formation and areas for strengthening. The authors identify the main threats and risks to the financial security of small businesses. The main elements of the system of ensuring financial security of small businesses are characterized.
Keywords: small business, business entities, financial security, financial instruments, financial threats, financial resources, financial risks, elements of financial security.